(untitled) (Jurnal Bahasa, 2013)
This This article will analyse the syntactic properties of Malay and the types of serial verbs in Malay especially those prevalent in the Kedah and Melaka Malay dialects. Serial verbs can be roughly defined as containing two or more verbs in sequence such as the construction: NP V1 (NP2) V2 (NP3) without overt coordination or subordination markers. Based on this definition, six categories of serial verbs are postulated. The characteristics of serial verbs are also described. Baker (1989) discussed the types of serial verbs which are considered as proper serial verbs but which did not include motion serial verbs. Baker (1989) posits a few types of serial verbs which he regards as serial verb proper such as structure [VP V V N Det]. One type of structure, [VP V N V N ] that exists in Malay is the for example are an example of those which Baker did not consider as serial verbs. This article argues that directional serial verbs are legitimate serial verb constructions in Malay especially in DMK. Three diagnostic tests namely negation, extraction of arguments and intonation were applied to these serial verbs constructions. They demonstrate the difference in behavior among serial verbs versus the embedded or coordinate clauses. Keywords: process, clause, functional grammar, active process, mental process, situational process, experiential